KEPASTIAN HUKUM PEMEGANG HAK GUNA USAHA PT. PENITI SUNGAI PURUN DI KABUPATEN PONTIANAK PROVINSI KALIMANTAN BARAT TERHADAP GUGATAN MASYARAKAT - DEA RIZSKA (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1.  Prof. Dr. Muhd Yamin, SH, MS, CN2.  Prof. Dr. Syafruddin Kalo, SH, MHum3.  Dr. T. Keizerina Devi A, SH, CN, MHum Developing oil palm plantation needs a wide area, and this usually brings about conflicts. In this respect, PT. Peniti Sungai Purun is involved in conflict with the people surrounding the area since they complain about the distribution of the land concerning plasma model patnership at purun kecil village and peniraman village. The people claim that the oil palm plantation is unwise and lacks of consideration towards the people’s rights.The reseacrh problems were how about legal provision about the regulation on land ownership at PT. Peniti Sungai Purun, how about the obstacles in settling the dispute by PT. Peniti Sungai Purun as the leasehold holder againts the people’s complaint, how about legal certainty of PT. Peniti Sungai Purun as the leasehold holder againts the people’s complaint.Keywords : Legal Certainty, Leasehold Holder, People’s Complaint.